Porphyrin‐Based Porous Organic Frameworks as Oxygen Reservoirs to Overcome Tumor Hypoxia for Enhanced Photodynamic Therapy. Issue 8 (6th June 2019) - Wei, Gaofei; Huang, Liangfeng; Shen, Yifeng; Huang, Zeqian; Xu, Xiaoyu; Zhao, Chunshun
Abstract: Photodynamic therapy kills cancer cells by transferring energy from lasers to tumor‐dissolved O2 to generate highly cytotoxic reactive oxygen species using a photosensitizer. However, the effectiveness of PDT is impaired by the aggregation of photosensitizer and an inadequate oxygen supply in tumors. Here, to overcome above limitations, novel porous organic frameworks (POFs) are reported using photosensitizer porphyrin as building blocks connected through imine condensation reactions. Upon both characteristic with the high porosity and the large surface area, TAPP‐B4‐POFs exhibit excellent O2 carrying capacity. After carrying O2, O2 @TAPP‐B4‐POFs generate ROS efficiency in both normoxic and hypoxic environment, which can induce cancer cell apoptosis. Moreover, the antitumor experiment on 4T1 murine breast cancer model demonstrates that O2 @TAPP‐B4‐POFs can almost completely suppress tumor progression with good security. These results reveal that photosensitizer‐based POFs materials are promising candidates as oxygen reservoirs to overcome tumor hypoxia for enhanced photodynamic therapy. Abstract : In this work, a novel POF is synthesized using photosensitizer porphyrin as building blocks connected through imine condensation reactions. After carrying O2, O2 @TAPP‐B4‐POFs generate ROS efficiency in a hypoxic environment by overcoming hypoxia and enhancing PDT therapeutic effect. Moreover, O2 @TAPP‐B4‐POFs can almost completely suppress tumor progression with good security.